Unique mutations in non-structural proteins among sars-cov-2 Variants from Sabah, Malaysia - Krishnan Nair Balakrishnan; Nurul Elyani Mohamad; Chee, Wei Yew; Chong, Eric Tzyy Jiann; Ping, Chin Lee (Bentham Science Publishers, 2025)
Next-generation sequencing (NGS) is essential for monitoring SARS-CoV- 2 transmission and tracking of genomic evolution worldwide to identify the mutations associated with different infection rates. Sabah, Malaysia is the third-most populous state, accounting for approximately 10% of the country’s COVID-19 fatalities, underscoring the need for detailed genomic analysis of SARS-CoV-2 strains associated with this region. This study analysed 644 COVID-19 samples through whole-genome sequencing, supplemented by 1,458 additional Sabah COVID-19 sequences from the GISAID EpiCoV consortium. As of June 2024, samples from Sabah showed a 1:1 male-to-female ratio, with the highest representation in the 21-30 age group (n=404). The samples showed a relatively high mutation count, with a mode of 62 and an average of 56.9 mutations per sample. We documented 67,485 amino acid-changing SNP events (68.6% of the total), while silent SNPs represented 21.3% (20,918 events) and primarily occurred in the coding regions. Kota Kinabalu district has the highest mutation frequency, while Tawau district has the lowest. Although no distinct mutation pattern emerged across age groups, mutation frequency was generally high in individuals aged 0 to 25, followed by individuals aged 61 to 90 and those aged 26 to 60. Notably, ten unique coding mutations were identified, with A580P and S672P mutations in the NSP region affecting viral protein stability and rigidity. The presence of two unique mutations found in the Sabah population is absent from global databases like GISAID or Nextstrain, suggesting region-specific viral evolution. These mutations may have arisen due to local selection pressures and adaptation influenced by host genetics, transmission patterns, or therapeutic interventions. These findings provide valuable insights into the spread and evolution of SARS-CoV-2 strains in Sabah and the surrounding areas.